A study on determining the views of people on the COVID-19 vaccine - Tengilimoğlu, Dilaver; Yiğit, Arzu; Kalmuk, Gülhan; Kılıç, Taşkın; Tengilimoğlu, Onur; Demirbaş, Ali Rıza (Intelektual Pustaka Media Utama, 2024)
The aim of this study was to determine the views and approaches of the public to the COVID-19 vaccination in Turkey. We conducted a descriptive study using the data collection method which is among quantitative research methods and the screening technic for analysis. The data collection method for the study was an online survey. The 38.4% of participants stated they would consider getting vaccinated, 50.6% stated they were undecided, and 11% stated they would not consider getting vaccinated. There was also a significant correlation between the participants' desire to be vaccinated and their educational level, age, and socioeconomic status. The belief that being diagnosed with COVID-19 creates stigmatization/labeling in society, as well as the belief that the vaccine will have serious side effects, reduce the possibility of getting vaccinated. The study also found that there is a positive correlation between the belief that the vaccine can defeat the virus and the possibility of getting vaccinated. Understanding the causes and effects of vaccine hesitancy and rejection is essential for developing effective immunization programs. Policy makers should inform the public to increase the trust in the vaccine and dispel the misinformation and rumors about COVID-19.